From Informing to Interacting? Exploring the European Commission's Communication Strategy "to be all ears" - Annelies Van Brussel (Journal of Contemporary European Research, 2014)
Since 2001 the European Commission has paid increasing attention to two-way communication in its institutional communication strategy. Besides informing the public, the Commission’s strategy has become orientated towards listening to and engaging in a dialogue with citizens. This article explores the rhetoric of the Commission regarding its institutional communication strategy from 2001 to the present time and studies in depth the dialogic dimension of this strategy. This contribution extends the study of the Commission’s communication strategy by offering new insights into the development of the dialogic approach and the Commission’s current understanding of communication. Furthermore, defining institutional two-way communication as a means to facilitate a link between decision making and public opinion, I contribute to the debate on the European public sphere. The data used for the analysis originate from document analysis and semi-structured elite interviews with Commission officials. The analysis indicates the gradual nature of the shift between 2001 and 2009 from a one-way informing approach to a two-way communicating approach. The dialogic dimension in the Commission’s communication strategy is found to be more restricted in terms of subjects for discussion and facilitation. There are indications that engaging in a dialogue and interaction have been played down and are being managed through other means outside the formal communication strategy.